问题 解答题
4
9
÷[
4
5
-(
1
5
+
1
3
)]
 
1
3
+3-(
1
4
+
1
12
3×(
2
15
+
1
12
)-
2
5
3
4
×
5
7
×
4
3
-
1
2
15
16
+(
7
16
-
1
4
)÷
1
2
23-
8
9
×
3
8
÷
1
27
1
3
-
1
4
)÷
1
2
+
5
6
1
2
×3+
1
2
÷
1
5
2
3
+(
4
7
+
1
2
)×
7
25
5
6
+
2
5
÷4.
答案

4
9
÷[
4
5
-(
1
5
+
1
3
)],

=

4
9
÷[
4
5
-
1
5
-
1
3
],

=

4
9
÷(
3
5
-
1
3
),

=

4
9
÷
4
15

=

5
3

1
3
+3-(
1
4
+
1
12
),

=

1
3
+3-
1
3

=3;

③3×(

2
15
+
1
12
)-
2
5

=3×

2
15
+3×
1
12
-
2
5

=

2
5
+
1
4
-
2
5

=

1
4

3
4
×
5
7
×
4
3
-
1
2

=

3
4
×
4
3
×
5
7
-
1
2

=

5
7
-
1
2

=

3
14

15
16
+(
7
16
-
1
4
)÷
1
2

=

15
16
+
3
16
÷
1
2

=

15
16
+
6
16

=

21
16

⑥23-

8
9
×
3
8
÷
1
27

=23-9,

=14;

⑦(

1
3
-
1
4
)÷
1
2
+
5
6

=

1
12
÷
1
2
+
5
6

=

1
6
+
5
6

=1;

1
2
×3+
1
2
÷
1
5

=

1
2
×(3+5),

=

1
2
×8,

=4;

2
3
+(
4
7
+
1
2
)×
7
25

=

2
3
+
15
14
×
7
25

=

2
3
+
3
10

=

29
30

⑩8×

5
6
+
2
5
÷4,

=

20
3
+
1
10

=

203
30

单项选择题
问答题 简答题